2022
DOI: 10.3390/ijerph192316033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Core Stability Training on Functional Movement Patterns in Tennis Players

Abstract: The aim of this study was to assess the effects of a six-week core stability training program on the fundamental movement pattern assessed using the Functional Movement Screen Test in tennis players. The study group consisted of 160 subjects (74 women, 86 men) with a mean age of 20.26 ±1.55. The Functional Movement Screen Test (FMS™), as well as the core stability tests including the lateral trunk muscles endurance test (the side bridge test), the abdominal muscles endurance test and the trunk extensors muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Xiao et al [23], showed a significant increase in physical performance in the experimental group, compared with controls, after 6 weeks of core training. Fernandez et al [24] and Majewska et al [25] obtained the same results after 6 weeks of specific core training and prevention exercises in a group of young, elite tennis players. Wang et al [26] confirmed that 9 weeks of core training positively improved tennis players' core strength.…”
Section: Discussionmentioning
confidence: 58%
“…Xiao et al [23], showed a significant increase in physical performance in the experimental group, compared with controls, after 6 weeks of core training. Fernandez et al [24] and Majewska et al [25] obtained the same results after 6 weeks of specific core training and prevention exercises in a group of young, elite tennis players. Wang et al [26] confirmed that 9 weeks of core training positively improved tennis players' core strength.…”
Section: Discussionmentioning
confidence: 58%
“…In one such study examining the effects of core strengthening training on physical and athletic performance in elite handball players, significant improvements were observed in physical components, but not in handball-specific athletic performance [ 14 ]. Similarly, a study investigating the effects of core exercises on functional movement patterns in adult tennis players reported significant changes in all functional movement screen test results [ 48 ]. Lust et al [ 49 ] also found that a six-week training program, combining open and closed kinetic chain plyometric exercises with core stability exercises, improved core endurance in baseball athletes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of core stability training (CST) on athletic performance has been and continues to be studied. Previous studies revealed that a CST program increased some parameters of general performance and sportspecific performance in badminton, handball, baseball, basketball, football, swimming, tennis, rhythmic gymnastics, and modern dance [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Body posture control ability is an important criterion for the expression of technical movements, the display of morphological artistic aesthetics and the evaluation of competition results [2] , Posture is de ned as the combination of the position of the joints in relation to each movement of the body, and the ideal posture can be de ned as the one in which the joints are subjected to the least stress and therefore use the least energy [3] .The FMS test is a valid, sensitive and reliable tool for functional assessment of athletic populations [4,5,6] , and the FMS screening (Function Movement Screen (FMS)) consists of seven functional tasks involving movement patterns of the trunk, upper and lower limbs. Each task is scored according to ability, with a maximum score of 3 indicating good task performance (21 points indicates a full score) [7] .The FMS has a good effect on improving athletes' own de ciencies and di cult technical movements, and has the effect of screening for injury risk [8] .Functional training with the FMS has been shown to be effective in improving athletes' balance, injury prevention, stability and improving athletic performance [9,10,11] . To improve FMS scores, training systems such as no-load training, kettlebells, core boards and cable machines, training forms such as TRX, Omnia, CrossFit and BOSU are recommended to develop muscular strength, bilateral symmetry, trunk stability and sports FMS scores [12,13] .Several studies have shown that functional training has a signi cant effect on core stability and movement balance [14] , and that professional athletes in particular tend to have postural de cits or spinal curvature de cits in the sagittal and frontal planes [15] , and therefore in competition, As athletes often suffer from potential functional impairments that affect the perfect performance of di cult movements and movement techniques [16] , that only physically t athletes can perform combinations of high technical speci cations and standards and achieve excellent results [17] , and functional movement screening can accurately assess the functional de ciencies of athletes in the process of exercise and develop training program that match the characteristics of the body and specialty to compensate for the de ciencies in their own qualities.…”
Section: Introductionmentioning
confidence: 99%